Desertification Process in The North-Eastern Part of The Aravalli Mountains Fringing the Thar Desert, India - Raghav, K S (Annals of Arid Zone, 2016)
The distribution of saod dunes in space and time and nature of present drainagesystem in the north-eastern part of the Aravalli Mountains indicate agradual desertification. The natural and anthropogenic causes of desertificationhave been discLlssed.